Health care use before and after intensive care unit admission—A nationwide register‐based study. Issue 3 (7th December 2020) - Estrup, Stine; Thygesen, Lau C; Poulsen, Lone M; Gøgenur, Ismail; Mathiesen, Ole
Abstract : Background: The aim of this study was to describe healthcare utilization of patients admitted to ICU before and after ICU admission. Methods: Register‐based study including adult patients discharged from ICU between January 1st, 2011 and December 31st, 2014. Reference group was a sex‐ and age‐matched population not admitted to an ICU in the study period. Outcomes were hospital admissions, contacts to general practitioner or emergency services and municipality services from 1 year before ICU admission and up to 3 years after. Results: The study included 82 384 patients and an equal number of reference persons. Of patients with ICU admission, 48% were married (reference group 57%), 48% had elementary school education (reference group 38%) and 18% had a Charlson co‐morbidity score of 5+ (4% in reference group). We found that 51% of patients with an ICU admission had been admitted to hospital in the year before ICU admission (reference group 15%) and 97% had a contact to a general practitioner (reference group 89%) in the same period. Conclusions: Patients admitted to an ICU had increased use of both primary and secondary health care both before and for years after ICU treatment, even after adjustment for comorbidities and socio‐economic factors.